Mediating Protracted Conflict - Harris, A. (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2005)
ABSTRACT This article contains an examination of two instances of protracted communal conflict, in Sudan and Sri Lanka. In my view the level of hostilities between the insurgent group and the national government in each case has risen to a level equivalent to that of warfare between sovereign states. The insurgent groups in each case, in Sudan, the Sudan People's Liberation Movement/Army (SPLM/SPLA), and in Sri Lanka, the Liberation Tigers of Tamil Eelam (LTTE), appear to have acquired certain attributes of belligerency. These include the capacity to maintain military control of territory, the ability to administer that territory effectively coercionfree, and a fidelity to the implementation of international human rights law. It is contended these attributes may provide particular mediators, for Sudan, the Intergovernmental Authority on Development (IGAD), and for Sri Lanka, the Norwegian government's Ministry of Foreign Affairs, an ability to move governments from the practice of "discounting" or disparaging the insurgents during negotiations, to a practice of negotiating with the latter in a sober vein. The supposition is that this "movement" on the part of the government renders a ceasefire more attainable.